Bibliometric and visualized analysis of the application of nanotechnology in glioma - Du, Xue; Chen, Chunbao; Yang, Lu; Cui, Yu; Tan, Bangxian (Frontiers in Pharmacology, 2022)
Background: Glioma is the most prevalent malignant tumor in the central nervous system (CNS). With the flourishing development of nanotechnology, targeted nano-therapy for glioma has become a hot topic of current research by using the characteristics of nanoparticles（NPs） such as its easier to pass the BBB, degradable and, controllable release of drugs in the brain. The purpose of this study is to visualize the scientific achievements and research trends of the application of nanotechnology in glioma. Methods: We searched the literature related to glioma nanotechnology in Web of Science （WOS）. The bibliometric and visual analysis was performed mainly using CiteSpace, VOSviewer and R software, for countries/regions, authors, journals, references and keywords associated with the field. Results：A total of 3290 publications from 2012 to June 2022 were searched, and 2041 literatures were finally obtained according to the search criteria, with an average growth rate (AGR) of 15.22% from 2012 to 2021. China published 694（ 20.99%), followed by USA (480, 20.70%). The institution with the highest number of publications is Fudan Univ (111, 13.16%). HUILE GAO (30) and XINGUO JIANG (30) both published the largest number of papers. STUPP R (412) was the most cited author. The degree of collaboration (DC) among countries/regions, institutions, and authors is 23.37%, 86.23%, and 99.22%, respectively. INTERNATIONAL JOURNAL OF NANOMEDICINE published the largest number of publications (81), followed by BIOMATERIALS (73). BIOMATERIALS (1420) was the most cited journal.The high frequency of keywords was drug delivery (487), followed by nanoparticle (450), indicates that nanoparticles (NPs) as a carrier for drug delivery is a hot topic of current research and a direction of continuous development. Conclusion: In recent years, nanotechnology have attracted much attention the medical field. Cooperation and communication between countries/regions and institutions need to be strengthened in future research to promote the development of nanomedicine. Nanotherapeutic drug delivery systems (NDDS）can enhance drug penetration and retention in tumor tissues, improve drug targeting, and reduce the toxic side effects of drugs, which has great potential for the treatment of glioma and has become the focus of current research and future research trends in the treatment of glioma.